Human Resource (HR) Practices - A Comprehensive Review - Sonar, Ashwini; Pandey, Rajesh Kumar (Management Journal for Advanced Research, 2023)
The Human Resource (HR) practices are critical cornerstone in contemporary organizational management. The field of HR has evolved significantly over the years, transitioning from a primarily administrative function to a strategic partner in achieving business objectives. Today, HR professionals are responsible for aligning HR practices with the organization's goals, ensuring that the right talent is in place, and creating a culture that supports high performance and employee well-being. Amidst the world of Technology, even HR is having its analytical wing and almost all function of HR is getting routed through the HR Analytics domain. This comprehensive review, led by researchers, delves into the multifaceted landscape of HR practices, exploring their significance, evolution, and benefits on organizational success. With a focus on both theoretical frameworks and real-world applications, the researchers examine the spectrum of HR practices, ranging from recruitment and selection to performance management and employee development. Employing a Descriptive and Exploratory Research design, this study encompasses both Primary and Secondary data. Primary data takes the form of interviews with HR Heads from five companies, offering insights into the HR practices of organizations. The research aims to understand the essence and significance of HR practices, while also investigating the benefits these practices bring to organizations. This study provides valuable insights into HR practices and highlights their adaptive nature in various organizational contexts. The analysis presented in this paper serves as a resource for HR professionals, managers, and researchers seeking to enhance their understanding of HR practices that drive organizational excellence. By critically assessing best practices, challenges, and emerging trends, this research contributes to the broader discussion on HR practices' impact on organizational success.